Association of sex with the global burden of glaucoma: an analysis from the global burden of disease study 2017. Issue 5 (7th January 2020) - Ye, Xin; She, Xiangjun; Shen, Lijun
Abstract: Purpose: To investigate the association of sex with the global burden of glaucoma by year, age and socio‐economic status using disability‐adjusted life years (DALYs). Method: The global, regional and national sex‐specific DALY numbers, crude DALY rates and age‐standardized DALY rates caused by glaucoma, by year and age, were obtained from the Global Burden of Disease Study 2017. Human development index (HDI) in 2017 as a national socio‐economic indicator was obtained from the Human Development Report. t ‐Test and linear regression were performed to explore the association between sex difference in age‐standardized DALY rates and HDI. Results: Globally, changes in glaucoma DALY number and crude rates were similar of both sexes between 1990 and 2017. After controlling for population size and age structure, age‐standardized DALY rates decreased consistently from 10.7 in 1990 to 9.4 in 2017 among men and from 8.8 in 1990 to 8.0 in 2017 among women. In 2017, the global average age‐standardized DALY rates were 11.6 ± 8.6 (mean ± standard deviation) in women and 14.9 ± 12.1 in men. The sex difference in age‐standardized DALY of 195 countries was significant ( t  = 3.109; p < .01) in 2017. Men had higher rates than women of the same age, and sexual differences increased with age. t ‐Test revealed that age‐standardized DALY rates among men were higher than those among women for low‐HDI countries ( t  = 3.102; p < .01) and high‐HDI countries ( t  = 2.110; p < .05). The difference (male minus female) in age‐standardized DALY rates (standardized β  = −0.434, p < .001) and the female‐to‐male age‐standardized DALY rate ratios (standardized β  = −0.315, p < .001) were inversely correlated with HDI. Conclusion: Although global glaucoma health care is progressing, sexual differences in glaucoma burden showed little improvement in the past few decades. Worldwide, men have higher glaucoma burden than women. Older age and lower socio‐economic status are associated with greater sex differences in glaucoma burden. Our findings may enhance public awareness of sexual differences in global glaucoma burden and emphasize the importance of making sex‐sensitive health policy to manage global vision loss caused by glaucoma.